2001
DOI: 10.1007/s11746-001-0304-1
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of estolides from oleic and saturated fatty acids

Abstract: Oleic acid and various saturated fatty acids, butyric through stearic, were treated with 0.4 equivalents of perchloric acid at either 45 or 55°C to produce complex estolides. Yields varied between 45 and 65% after Kugelrohr distillation. The estolide number (EN), i.e., the average number of fatty acid units added to a base fatty acid, varied as a function of temperature and saturated fatty acid. The shorter-chain saturated fatty acids, i.e., butyric and hexanoic, provided material with higher degrees of oligom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
87
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 93 publications
(93 citation statements)
references
References 23 publications
6
87
0
Order By: Relevance
“…On the contrary, estolide viscosities significantly decrease after 12h reaction time, a fact related to a lower molecular weight. This result confirms that estolide viscosity is controlled by the oligomerization degree (Cermak et al, 2001). The viscosity index for the estolides synthesized in this work was 178 Ϯ 5, regardless of reaction time, slightly lower (7%) than that obtained for olein.…”
Section: Synthesis Of Estolidessupporting
confidence: 84%
See 1 more Smart Citation
“…On the contrary, estolide viscosities significantly decrease after 12h reaction time, a fact related to a lower molecular weight. This result confirms that estolide viscosity is controlled by the oligomerization degree (Cermak et al, 2001). The viscosity index for the estolides synthesized in this work was 178 Ϯ 5, regardless of reaction time, slightly lower (7%) than that obtained for olein.…”
Section: Synthesis Of Estolidessupporting
confidence: 84%
“…Estolides are a class of ester resulting from the reaction between a carboxylic group in a fatty acid molecule and an unsaturation in another fatty acid molecule to form an ester linkage (Isbell et al, 1994, Isbell et al, 2000, Cermak et al, 2001. The number of these linkages determines the structure and properties of estolides.…”
mentioning
confidence: 99%
“…Typically, estolides are a class of ester resulting from the reaction between a carboxylic group in a fatty acid molecule and an unsaturation in another fatty acid molecule to form an ester linkage , Isbell et al, 2000, Cermak et al, 2001. The number of these linkages determines the structure and properties of estolides.…”
Section: Characterization Techniquesmentioning
confidence: 99%
“…The capping fatty acid of the estolide was evaluated for the impact of chain length on pour points (Cermak and Isbell 2001;Cermak and Isbell 2002;Cermak and Isbell 2009). Table 8 provides a summary of the work by Cermak and Isbell (2002) which demonstrated that a decanoyl capping group for the estolide provided the lowest pour points within this series.…”
Section: Estolides From Unsaturated Fatty Acidsmentioning
confidence: 99%